Control of T cell effector functions by miRNAs. (28th July 2018) - Inácio, Daniel P.; Amado, Tiago; Silva-Santos, Bruno; Gomes, Anita Q.
Abstract: The differentiation of effector T cells is a tightly regulated process that relies on the selective expression of lineage-defining master regulators that orchestrate unique transcriptional programs, including the production of distinct sets of effector cytokines. miRNAs are post-transcriptional regulators that are now viewed as critical players in these gene expression networks and help defining cell identity and function. This review summarises the role of individual miRNAs in the regulation of the differentiation of effector T cell subsets, including CD4 + T helper cells, cytotoxic CD8 + T cells and innate-like NKT cells. Moreover, we refer to miRNAs that have been identified to affect simultaneously two or more effector T cell populations, impacting on the balance between effector T cells in vivo, thus constituting potential biomarkers or targets for therapies aiming at boosting immunity or controlling autoimmunity. Highlights: miRNAs as key post-transcriptional regulators of effector T cell differentiation. miRNAs that act as regulators of CD4 T cell- (Th1, Th2, Th7, Tfh and Treg cells), CD8 + T cell- and NKT cell- differentiation. Physiological relevance of miRNAs that affect simultaneously two or more effector T cell populations.